Identification of Inhibitors of Yellow Fever Virus Replication Using a Replicon-Based High-Throughput Assay - Patkar, Chinmay G. (American Society for Microbiology (ASM), 2009)
Flaviviruses cause severe disease in humans and are a public health priority worldwide. However, no effective therapies or drugs are commercially available yet. Several flavivirus replicon-based assays amenable to high-throughput screening of inhibitors have been reported recently. We developed and performed a replicon-based high-throughput assay for screening small-molecule inhibitors of yellow fever virus (YFV) replication. This assay utilized packaged pseudoinfectious particles containing a YFV replicon that expresses Renilla luciferase in a replication-dependent manner. Several small-molecule compounds with inhibitory activity at micromolar concentrations were identified in the high-throughput screen. These compounds were subsequently tested for their inhibitory activities against YFV replication and propagation in low-throughput assays. Furthermore, YFV mutants that escaped inhibition by two of the compounds were isolated, and in both cases, the mutations were mapped to the NS4B coding region, suggesting a novel inhibitory target for these compounds. This study opens up new avenues for pursuing the nonenzymatic nonstructural proteins as targets for antivirals against YFV and other flaviviruses.